Effect of Polywave and Monowave Light Curing Units on the Microtensile Bond Strength and Failure Types of Different Bulk-Fill Resin Composites: An in vitro Study - Castro-Ramirez L; Espinoza-Salcedo M; Huamani-Echaccaya J; Ladera-Castañeda M; Cervantes-Ganoza L; Hernández-Huamaní E; Aroste-Andía R; Gavilán-Chávez P; Cayo-Rojas C (Dove Medical Press, 2024)
Leonor Castro-Ramirez,1,2 María Espinoza-Salcedo,1 José Huamani-Echaccaya,3 Marysela Ladera-Castañeda,4 Luis Cervantes-Ganoza,5 Emily Hernández-Huamaní,3 Rosa Aroste-Andía,3 Percy Gavilán-Chávez,3 César Cayo-Rojas2 1Postgraduate School, Universidad Privada Antenor Orrego, Trujillo, Peru; 2School of Stomatology, Universidad Privada San Juan Bautista, Lima, Peru; 3School of Stomatology, Universidad Privada San Juan Bautista, Ica, Peru; 4Faculty of Dentistry and Postgraduate School, Research Team "Salud Pública - Salud Integral", Universidad Nacional Federico Villarreal, Lima, Peru; 5Faculty of Stomatology, Universidad Inca Garcilaso de la Vega, Lima, PeruCorrespondence: César Cayo-Rojas, Universidad Privada San Juan Bautista, School of Stomatology, Av. José Antonio Lavalle 302-304 (Ex Hacienda Villa); Chorrillos, Lima, Peru, Email cesarcayorojas@gmail.comAim: This study aimed to evaluate the effects of polywave and monowave light-emitting diode curing units on the microtensile bond strength and failure types of three bulk-fill resin composites.Materials and Methods: This in vitro experimental study was performed on 180 microbars obtained from human third molars and were distributed into 12 groups according to the type of bulk-fill resin composite and the light-curing unit. Third molars were restored using Filtek One Bulk Fill Restorative, Tetric® N-Ceram Bulk Fill, and Opus Bulk Fill resin composites was light-cured with Elipar Deep Cure L and Valo in three modes: standard, high power, and extra power. Subsequently, microtensile analysis was carried out with a universal testing machine and the type of failure with an optical stereomicroscope. For statistical analysis, the Kruskal-Wallis H-test was used, with the Bonferroni post hoc test and Fisher's exact test, considering a significance of p< 0.05.Results: There were significant differences in the microtensile bond strength between the Filtek One Bulk Fill restorative and Opus Bulk-Fill (p = 0.042) when light was cured with the polywave unit at standard power. On the other hand, the Filtek One Bulk Fill Restorative and Opus Bulk Fill resins showed significant differences in microtensile bond strength when light was cured with the monowave unit compared with the polywave unit (p< 0.05).Conclusion: The presence of alternative photoinitiator systems that are more reactive than camphorquinone produced higher microtensile bond strength in Tetric N-Ceram Bulk Fill and Opus Bulk Fill resins when light-cured with a high and standard polywave unit, respectively, compared to Filtek One Bulk Fill resins. Finally, Tetric N-Ceram Bulk Fill and Opus Bulk Fill resins had the highest percentage of mixed failures, while Filtek One Bulk Fill resin had adhesive failures, which was related to its lower microtensile bond strength.Keywords: dental materials, resin composite, bulk fill, bond strength, monowave, polywave, light curing units